2017
DOI: 10.1021/acs.biomac.7b01434
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Crystallite Orientation of Poly(ethylene oxide)/Cellulose Nanofiber Composite Films

Abstract: The crystallite orientation and crystallographic domain structure of poly(ethylene oxide) (PEO) in cellulose nanofiber-incorporated (CNF-incorporated) PEO films developed for packaging materials were observed using wide-angle X-ray diffraction for different CNF filling ratios. When a CNF filling ratio of <10 wt % was used, the molecular chains in the PEO crystallite region were oriented in a direction perpendicular to the surface of the film; however, when the ratio was >50 wt %, the PEO molecular chains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…In this regard, the use of an amphiphilic compatibilizer, such as poly­(ethylene oxide) (PEO), a linear polymer with a molecular weight ranging from 100 000 to 7 000 000 g/mol, could represent a greener alternative due to its nontoxicity, water solubility, biodegradability, and biocompatibility. , A number of studies have shown that, owing to the formation of strong hydrogen bonds, PEO favors the dispersion of cellulosic materials in the polymer blends, improving their thermal stability as well as the interfacial interaction and the mechanical properties of the resulting composites. For example, Yong et al reported the improvement in the mechanical properties of PVA/PEO nanocomposite films, prepared by solvent casting method, reinforced with up to 6 wt % by cellulose nanofibers (CNFs) or cellulose nanocrystals (CNCs). However, the effect of PEO as a compatibilizer for the melt processing of thermoplastic composites containing cellulose has been hardly investigated, and it was demonstrated exclusively for low loadings, typically 1–5 wt % of cellulose fillers.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the use of an amphiphilic compatibilizer, such as poly­(ethylene oxide) (PEO), a linear polymer with a molecular weight ranging from 100 000 to 7 000 000 g/mol, could represent a greener alternative due to its nontoxicity, water solubility, biodegradability, and biocompatibility. , A number of studies have shown that, owing to the formation of strong hydrogen bonds, PEO favors the dispersion of cellulosic materials in the polymer blends, improving their thermal stability as well as the interfacial interaction and the mechanical properties of the resulting composites. For example, Yong et al reported the improvement in the mechanical properties of PVA/PEO nanocomposite films, prepared by solvent casting method, reinforced with up to 6 wt % by cellulose nanofibers (CNFs) or cellulose nanocrystals (CNCs). However, the effect of PEO as a compatibilizer for the melt processing of thermoplastic composites containing cellulose has been hardly investigated, and it was demonstrated exclusively for low loadings, typically 1–5 wt % of cellulose fillers.…”
Section: Introductionmentioning
confidence: 99%
“…at 75 wt.%. 25 In the pattern of C70P30 (10 K), the ring was convergent to the side of the detector and the peak-area-ratio of P z to P xy was around 0.4, revealing a dominant flat-on orientation of PEG. As the content of PEG increased, the value of P z /P xy decreased continuously and came to the lowest 0.1 when PEG content was 50 wt.%, indicating that the PEG had the best flat-on orientation in this sample.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In detail, the absorption bands at 3266 (1), 3338 (2), and 3450 cm −1 (3) were assigned to the intermolecular hydrogen bonds between O3-H and O6 and intramolecular hydrogen bonds between O3-H and O5, or O2-H and O6, respectively, according to the literature. 25,37 The absorption bands (4) at 3513−3579 cm −1 were assigned to the free O2-H and O6-H. 37 In these spectra of CNC/PEG composites, the emerging absorption bands (5) at 3408 cm −1 with the increasing weight percentage of PEG were assigned to the formation of hydrogen bonds between CNCs and PEG. 25 After peak fitting (Figure S5 and Figure 1c), it is clear that the area proportion of peak (1) and peak (3&4) decreased notably with the increasing weight percentage of PEG while the absorption bands (5) emerged gradually.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the uncured composite film, the peak at 19.2° was from PEO, and the peak at ∼23° was a combination of the CNF peak at 22.7° and the PEO peak at 23.3°. It is well known that hydrogen bonding can form between PEO and CNFs, and the interaction can affect PEO crystallization in terms of crystal orientation and crystal size. Because the two peaks around 23° are so close, it is difficult to clearly discern the changes of the peaks from their merged peak. However, by comparing the patterns for the composite films before and after curing (Figure e inset), it is clear that the intensity and sharpness of the part of the merged peak that represents the PEO crystals decreased after the curing.…”
Section: Resultsmentioning
confidence: 99%